Alternative splicing of OsLG3b controls grain length and yield in japonica rice. Issue 9 (24th March 2018) - Yu, Jianping; Miao, Jinli; Zhang, Zhanying; Xiong, Haiyan; Zhu, Xiaoyang; Sun, Xingming; Pan, Yinghua; Liang, Yuntao; Zhang, Qiang; Abdul Rehman, Rashid Muhammad; Li, Jinjie; Zhang, Hongliang; et al.
Summary: Grain size, one of the important components determining grain yield in rice, is controlled by the multiple quantitative trait loci (QTLs). Intensive artificial selection for grain size during domestication is evidenced in modern cultivars compared to their wild relatives. Here, we report the molecular cloning and characterization of OsLG3b, a QTL for grain length in tropical japonica rice that encodes MADS‐box transcription factor 1 (OsMADS1). Six SNPs in the OsLG3b region led to alternative splicing, which were associated with grain length in an association analysis of candidate region. Quantitative PCR analysis indicated that OsLG3b expression was higher during the panicle and seed development stages. Analysis of haplotypes and introgression regions revealed that the long‐grain allele of OsLG3b might have arisen after domestication of tropical japonica and spread to subspecies indica or temperate japonica by natural crossing and artificial selection. OsLG3b is therefore a target of human selection for adaptation to tropical regions during domestication and/or improvement of rice. Phylogenetic analysis and pedigree records showed that OsLG3b had been employed by breeders, but the gene still has much breeding potential for increasing grain length in indica . These findings will not only aid efforts to elucidate the molecular basis of grain development and domestication, but also facilitate the genetic improvement of rice yield.